Evaluation of the practicum in the Mercado Artesanal Guayaquil and recommendation for future practicum - Acosta Cinthia, Bonilla Rossy (2003)
Methodology: introduction, data collection, techniques or procedures observation, interview guide, evaluation of materials, cassette evaluating format, written material evaluating format, diagnostic test, scoring procedures language proficiency scale chart, pilot class, planning an oral class lesson
Facultad-Ecología humana
Keywords: Tesis